2009
DOI: 10.1109/tasc.2009.2017880
|View full text |Cite
|
Sign up to set email alerts
|

DC and AC Shielding Properties of Bulk High-Tc Superconducting Tubes

Abstract: Abstract-We have studied numerically and experimentally the magnetic flux penetration in highsuperconducting tube subjected to a uniform magnetic field parallel to its long axis. This study is carried in view of designing low-frequency magnetic shields by exploiting the diamagnetic properties of high-superconducting ceramics. We have measured the field attenuation for applied magnetic fields in the frequency range 5 mHz-0.1 Hz by Hall probe measurements and at audio frequencies using a sensing coil. A simple 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…First, the limiting field in the transverse configuration B lim is ≈ 18 mT, which corresponds to the best values reported so far for superconducting magnetic shieding at the liquid nitrogen temperature [9,11,[12][13][14][15]. Second, the average critical current density J c = 350 A/cm² corresponds to the self field ~ 20 mT at the surface of the cylinder.…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…First, the limiting field in the transverse configuration B lim is ≈ 18 mT, which corresponds to the best values reported so far for superconducting magnetic shieding at the liquid nitrogen temperature [9,11,[12][13][14][15]. Second, the average critical current density J c = 350 A/cm² corresponds to the self field ~ 20 mT at the surface of the cylinder.…”
Section: Methodssupporting
confidence: 69%
“…For θ = 0° (i.e. H ⊥ slits), the distribution of J z exhibits an eye-shape structure which is similar to that found in an infinite cylinder without any slit [15,27]. This is an anticipated result since the shielding currents in the median plane are always perpendicular to the applied field, i.e.…”
Section: Distribution Of Shielding Currentssupporting
confidence: 54%
See 2 more Smart Citations
“…4 Until recently, HTS shields have been made out of bulk materials. 5,[8][9][10] The significant progress in manufacturing the second generation ͑2G͒ coated conductors 11,12 has opened a possibility that they can be used as a material for magnetic screens. A recent study 13 reported the use of YBCO coated conductors to attenuate ac magnetic fields at low frequencies ͑10-100 Hz͒.…”
Section: Introductionmentioning
confidence: 99%